Building Brand Image Perguruan Tinggi: BUILDING BRAND IMAGE PERGURUAN TINGGI - Rumina Rumina (LPPM IAI Hasanuddin Pare-Kediri, 2018)
Building an image of a college requires marketing terms that have an important role for the survival of universities, because today there are no organizations, both business and non-business organizations that can be separated from marketing.Marketing begins with internal marketing, namely communicating to staff about things that happen in the institution, so that staff have the opportunity to give feedback ideas. If this internal customer is run properly, it will be able to boost the wider external marketing. Marketing conducted by universities is oriented to customer satisfaction in this case students, to attract the interest of college students need to pay attention to several categories of how prospective students see universities that will be their choice, including; (1) universities that are more pretisius (2) problems of place or location of campus (3) superior private universities in one part only (4) universities that do not discriminate student admissions in any department (5) universities are not only dominated by upper economic circles, but also by the lower middle class. (6) the dissemination of brochures, banners, throughout the university segment must be intensified.Building a positive image of higher education begins with improving conditions: (a) internal factors, namely curriculum factors, concentration of education, teaching staff, as well as graduate prospects, differentiation becomes an important element to place a product different from the others so that it becomes its own brand. (b) external factors such as the factor of regional autonomy, and the high cost of education, this factor influences the decline in the number of students. (c) As well as fostering cooperative relations between educational institutions and communities, the Board of Trustees, the Education Council, school committees, and educational foundations.